Unknown Popper: preface to the translation of the chapter «Interaction and consciousness» (Actual Problems of Mind, 2022)
Abstract. The article is designed to introduce the issues subjected to K. Popper's analysis in the so-called metaphysical period of his intellectual quest and, thereby, facilitate the reading and comprehension of the proposed translation of the fifth chapter from the book "Knowledge and the Body-Mind Problem: In Defence of Interaction". The author emphasizes that, in Ukraine, Popper is known predominantly as a political philosopher and a social science methodologist, and that fact corresponds to the early methodological period. In many ways, his views on classical philosophical problems remain misunderstood and misrepresented in the West. The mind-body problem is among such classic philosophical problems widely discussed in contemporary analytic philosophy; its quite original tentative solution of which is offered by K. Popper. In particular, he suggests looking at this problem in the light of three ideas: the autonomy of the world 3, emergent evolution, and the theory of the evolution of language. Using these ideas, Popper criticizes all known approaches to solving the mind-body problem: both monistic (behaviorism/physicalism and solipsism) and dualistic ones (parallelism and Cartesian interactionism). The value of the approach offered by K. Popper may lie in the fact that, on the one hand, it actualizes the ideas of many previous philosophers, in particular, Plato, R. Descartes, F. Bolzano, G. Frege, and, on the other hand, it attracts a wide range of modern scientists' ideas and concepts: K. Bühler's idea of the evolution of language, Ch. Darwin's idea of biological evolution, Ch. Peirce's fallibilism, K. Lorenz's ethology, E. Schrödinger's quantum mechanics, etc. The author believes that the familiarization with K. Popper's arguments can be useful for the contemporary discussion of the mind-body problem, which is conducted mainly in the physicalist terms of cognitive science and to a much lesser extent in the philosophical terms of the metaphysics of mind. The author also draws attention to the peculiarity of Popper's style of philosophizing, difficulties with the translation of some philosophical terms and demonstrates how Popper himself follows his philosophical principles of critical rationalism.
Keywords: K. Popper, the mind-body problem, consciousness, higher functions of language, three worlds, emergent evolution, objective knowledge, interactionism, critique of physicalism